VULNERABILITY ANALYSIS OF PANGUMBAHAN BEACH, WEST JAVA, AGAINST DAMAGE THREATS USING COASTAL VULNERABILITY INDEX (CVI) - Raihanah, Fadhilah
Coastal areas have dynamic conditions over time as a result of human activities as well as natural factors. Pangumbahan Beach in West Java is one of the beaches in Indonesia that is a natural habitat for turtle nesting. This beach is directly adjacent to the Indian Ocean so this place is often exposed to large waves. Human activities such as settlement construction, illegal logging, and cultivation have occurred on Pangumbahan Beach. These factors can have an impact on the destruction of coastal areas on Pangumbahan Beach. The purpose of this study was to determine the level of vulnerability of the six stations located on Pangumbahan Beach based on geomorphological variables, coastal slope, plant distance from the coast, width of the green belt, rate of change in coastline, average tides, and average significant wave height. Determination of vulnerability levels is carried out using the Coastal Vulnerability Index (CVI) through a scoring system for each variable. The vulnerability category of the CVI value consists of four classes, namely low with a CVI value of <20.5, medium with a value of 20.5-25.5, high with a value of 25.6-29.00, and very high with a value of >29.0. The results showed that Station 1 is included in the medium vulnerability category, stations 2, 5, and 6 are included in the high vulnerability category, while stations 3 and 4 are included in the very high vulnerability category.